Design of an accuracy study for position detection in football - Siegle, M.; Stevens, T.; Lames, M. (Journal of Sports Sciences, 2013)
Only a few studies have analysed the accuracy of position detection systems. All of them analysed distances and velocities, which are the outcome of calculations based on x,y positions. The objective of this study was to analyse the accuracy of dynamic x,y position measurement of a radar- and an image-based system in football. One and two runners performed five different runs on four different locations on a football pitch. X,y positions recorded by the radar-based and the image-based system were compared to x,y positions measured by a Laveg laser device. Accuracies were analysed by means of root mean square error (RMSE). Results showed that the radar-based system detects positions more accurately than the image-based system (P = 0.000). Mean RMSE of the radar-based system was 0.24 m, RMSE of the image-based system was 0.73 m. The image-based system was significantly influenced by the location of the run, whereas the radar-based system was not. Based on the results of this study, we conclude that the radar-based system is more valid in detecting x,y positions than the image-based system. Future studies should take advantage of the new test design which allows more precise statements on the accuracy of a position detection system.